Welfare-enhancing trade unions in an oligopoly with excessive entry - Marco de Pinto; Laszlo Goerke (Center for Economic Studies and ifo Institute (CESifo), 2019)
Trade unions are often argued to cause allocative inefficiencies and to lower welfare. We analyze whether this evaluation is also justified in a Cournot-oligopoly with free but costly entry. If input markets are competitive and output per firm declines with the number of firms (business stealing), there is excessive entry into such oligopoly. If trade unions raise wages above the competitive level, output and profits per firm decline, which could deter entry and thus improve welfare. We find that an increase in the union's bargaining power raises welfare if the (inverse) demand curve is (sufficiently) concave. We also show that collective bargaining loosens the linkage between business stealing and excessive entry.
Keywords: D43; J51; L13; 330; endogenous entry; oligopoly; trade union; welfare